Return to sports and work after partial shoulder replacement surgery - Bülhoff, Matthias; Sowa, Boris; Bruckner, Thomas; Zeifang, Felix (Der Orthopäde, 2017)
BackgroundShoulder hemiarthroplasty is a particularly attractive treatment option in young active patients, where revision surgery is an issue and a glenoid replacement might be necessary in the long run. These patients often ask about the possibility of returning to sport and work after surgery.ObjectiveThe purpose of this investigation was to analyze whether patients undergoing shoulder hemiarthroplasty (HSA) are able to successfully return to sports activities and work after surgery.Materials and methodsThis study included 42 patients treated with HSA. Two subgroups were built: patients who had participated in sports less than 5 years prior to surgery (group A: n = 29, 69%) and those who had not done so (group B: n = 13, 31%). Evaluation was based on a questionnaire asking about types of sports, frequency of sports activity, and the time taken to return to sports and work, as well as about limitations in occupational life.ResultsPatients’ mean age at the time of surgery was 56.3 ± 12.7 years in group A and 66.9 ± 13.8 years in group B. Mean follow-up was 5.5 years (range 2.5-12 years). In group A, 18 patients (62%) had participated in sports up to the time of surgery and 12 (41%) had returned to the same level of sports activity at final follow-up. The rate of return to preoperative sports activity was 67%. Swimming was one of the most favorable sports (92%). Of the cohort patients, 2 (5%) had to change their profession due to surgery. Most patients were retired at follow-up.ConclusionPatients who were sportingly active prior to HSA were able to return to sports after surgery in 67% of cases. This study confirms that patients treated by hemiarthroplasty of the shoulder joint can return to sports and work, even at medium-term follow-up.